General rules for the inductive characteristics of a piezoelectric structure and its integration with piezoelectric transformer for capacitive compensation. (9th March 2021) - Ju, Bin; Fang, Liang; Wang, Qing; Xu, Jiawen; Li, Guoli; Liu, Yongbin
Abstract: Additional inductive components are typically required in the driving applications of piezoelectric transformers (PTs) for the capacitive compensation. This compensation of such transformers can realize a zero-voltage switching state and obtain high efficiency. Recently, researchers have found that a piezoelectric structure can exhibit good inductive characteristics in the frequency range between resonance and anti-resonance, and it can be used as a substitute for an inductor in certain scenarios. This study first conducts a theoretical derivation and identifies the general rules for realizing an inductive piezoelectric structure. Then, the corresponding influencing factors of the inductive characteristics of the piezoelectric structure's impedance are analyzed. Finally, a piezoelectric inductor (PL) is integrated with a PT in accordance with the inductive characteristic of the former. Simulation and experiment studies are conducted to investigate the system level characteristics, and results indicate that the capacitance of the integrated PT (IPT) is well compensated within the corresponding frequency range. Simultaneously, the transfer characteristics of the IPT are better than those of the single PT. Hence, the PL can be extended for minimization and efficiency enhancement of piezoelectric sensors and actuators in the future.